2016
DOI: 10.1016/j.cmet.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1α Promotes Glutamine-Mediated Redox Homeostasis and Glycogen-Dependent Bioenergetics to Support Postimplantation Bone Cell Survival

Abstract: Cell-based therapy is a promising strategy in regenerative medicine, but the poor survival rate of the implanted cells remains a major challenge and limits clinical translation. We preconditioned periosteal cells to the hypoxic and ischemic environment of the bone defect site by deleting prolyl hydroxylase domain-containing protein 2 (PHD2), resulting in hypoxia-inducible factor 1 alpha (HIF-1α) stabilization. This strategy increased postimplantation cell survival and improved bone regeneration. The enhanced c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
159
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(166 citation statements)
references
References 43 publications
7
159
0
Order By: Relevance
“…In addition, recent findings indicate that the majority of in vitro expanded cells undergo apoptosis upon implantation (Stegen et al., 2016). A cause may be the need to instantly adjust to a compromised environment, since current culture conditions represent a rather non-physiological and abundant nutritional source.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent findings indicate that the majority of in vitro expanded cells undergo apoptosis upon implantation (Stegen et al., 2016). A cause may be the need to instantly adjust to a compromised environment, since current culture conditions represent a rather non-physiological and abundant nutritional source.…”
Section: Discussionmentioning
confidence: 99%
“…Functionally, stimulating glycolysis through activation of Hif1α signaling in preosteoblasts increases bone formation in vivo , indicating that reprogramming glucose metabolism is sufficient to promote osteoblast differentiation [103]. Moreover, Hif1α activation has been shown to promote bone healing partly through reprogramming of glucose metabolism, highlighting the clinical implications of understanding metabolic regulation in osteoblasts [104]. Recent studies have demonstrated that aerobic glycolysis is directly stimulated in response to osteogenic signals such as PTH and Wnt [105, 106].…”
Section: Glucose Metabolism In Osteoblastsmentioning
confidence: 99%
“…Decreased glutamine consumption by bone marrow stromal cells has been linked with impaired osteoblast differentiation associated with aging [147]. Moreover, increased glutathione production from glutamine in response to Hif1α has been shown to improve cell survival and bone repair in a critical-size tibial defect model [148]. In differentiating osteoblasts, glutamine anaplerosis fulfills part of the energetic requirement of bone formation in response to Wnt signaling.…”
Section: Amino Acid Metabolism In Osteoblastsmentioning
confidence: 99%
“…In this setting, their energy and redox metabolism is adapted in order to survive in hypoxic and nutrient deprived conditions . These adaptations were previously characterized in mouse PDCs . Interestingly, hypoxic culture conditions were shown to provoke recruitment of the glycogen stores to maintain the energy balance.…”
Section: Discussionmentioning
confidence: 99%